Why philosophy matters : 20 lessons on living large - Belliotti, Raymond A., 1948- (Cambridge Scholars Publishing, 2015)
This book demonstrates that philosophy matters to everyday living and that people who ignore the enduring, fundamental questions of life thereby unwittingly relinquish part of their humanity. The question - "How should I live my life?"--Along with cosmological inquiries about the nature of the world, animated Western philosophy during its earliest recorded years. Given that belief in the Greek and Roman gods failed to provide substantive guidelines for everyday living, philosophy arose in large measure as practical instruction in the art of living the good human life. Throughout history, philo.